Inter-Faith Dialogue, Peace Building and Conflict Transformation in Nigeria - Emmanuel Achus Jah; Damila Kevin Mabas (International Studies Journal)
Nigeria as a nation with diversity has religious plurality as one of its integral parts. Living in diversity surely is a formidable task. Such religious diversity has been a source of violent conflict owing to seemingly irreconcilable religious ideologies of the different faiths. This often makes it difficult for their adherents to look beyond their differences and search for common grounds upon which a shared community life can be built. Inter-faith dialogue is a peace-building activity which is carried out in an atmosphere of openness, quest for truth and reciprocal respect. It builds trust, clarifies misunderstandings, removes negative perceptions and stereotypes, and transforming enemy images and reconciliation which transform conflict from confrontation to cooperation. The challenges of interfaith dialogue are lack of focus by interfaith dialogue practitioners, proselytization by some participants, religious hegemony and religious extremism.The study recommends that the emphasis of citizenship Rights, poverty alleviation schemes, peace education,restorative justice system. The study concludes that the capacity of a society to continue to exist despite prevailing conflicts depends on its ability to devise the means of curbing the negative impact of such conflicts.